Carabalí and Culíes at El Cobre: African Slaves and Chinese Indentured Labourers in the Service of Swansea Copper, 19th Century - Evans, Chris (Revista de Historia Social y de las Mentalidades, 2017)
This article analyses the impact of the world of copper upon copper mining in Cuba from the late 1820s until the 1850s. The mounting british demand for copper resulted in an influx of capital, technological modernization and in a massive process of labor immigration. The transoceanic movement of laborers not only comprised britons (mostly cornish and welshmen), but it also meant the renewal of the slave trade, mostly of african carabalí and chinese coolies. Through an in depth research on archives of british companies and official data on the slave trade, this article sheds fresh light on the economic and cultural circulations of labor in Cuba.